2014
DOI: 10.1007/s00360-014-0824-1
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a urea sensitive lactate dehydrogenase from the liver of the African clawed frog, Xenopus laevis

Abstract: The African clawed frog, Xenopus laevis, is able to withstand extremely arid conditions by estivating, in conjunction with dehydration tolerance and urea accumulation. Estivating X. laevis reduce their metabolic rate and recruit anaerobic glycolysis, driven by lactate dehydrogenase (LDH; E.C. 1.1.1.27) enzymes that reversibly convert pyruvate and NADH to lactate and NAD(+), to meet newly established ATP demands. The present study investigated purified LDH from the liver of dehydrated and control X. laevis. LDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 35 publications
5
28
0
Order By: Relevance
“…The high-altitude population had a high activity of LDH in the heart (Table 1; Fig. 3), similar to what has been observed in various tissues of species that experience cold and hypoxic/anoxic environments (Rosser and Hochachka, 1993;Dawson et al, 2013;Shahriari et al, 2013;Katzenback et al, 2014). However, LDH in the heart likely facilitates lactate oxidation rather than production, a process that our data suggests might be enhanced in highland torrent ducks (Brooks, 1998;Gladden, 2004;Brooks, 2009).…”
Section: Enhanced Aerobic Capacity In the Gastrocnemius Muscle Of Higsupporting
confidence: 84%
“…The high-altitude population had a high activity of LDH in the heart (Table 1; Fig. 3), similar to what has been observed in various tissues of species that experience cold and hypoxic/anoxic environments (Rosser and Hochachka, 1993;Dawson et al, 2013;Shahriari et al, 2013;Katzenback et al, 2014). However, LDH in the heart likely facilitates lactate oxidation rather than production, a process that our data suggests might be enhanced in highland torrent ducks (Brooks, 1998;Gladden, 2004;Brooks, 2009).…”
Section: Enhanced Aerobic Capacity In the Gastrocnemius Muscle Of Higsupporting
confidence: 84%
“…It has been previously demonstrated that LDH from the liver of X. laevis maintains the control level of activity in vitro when urea is present. Katzenback at al. (2014) concluded that the PTM changes allowed the enzyme to function normally in the face of this protein denaturant.…”
Section: Discussionmentioning
confidence: 99%
“…In order to survive as long as possible, frogs are thought to reduce their metabolic rate and, when dehydration begins to affect oxygen distribution to tissues, they recruit anaerobic glycolysis to meet ATP demands (Malik and Storey 2009). It has further been demonstrated that X. laevis liver enzymes are modified in response to dehydration in order to adjust their function to the new metabolic demand and to ensure that when urea levels are high the enzymes retain their functionality (Katzenback et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, a greater percentage of arterial oxygen was being delivered to tissues in the aestivating frog than control. This relative decrease in oxygen content of venous blood in aestivating X. laevis is likely attributable to lactate-induced plasma acidification caused by enhanced lactate dehydrogenase (LDH) activity in dehydrated frogs at physiological concentrations of urea (Katzenback et al, 2014). At a low pH, hemoglobin has a higher release rate of oxygen and this could allow greater oxygen unloading in peripheral tissues when wholebody water content is reduced (Jokumsen and Weber, 1980).…”
Section: Metabolic Rate During Whole-body Dehydrationmentioning
confidence: 99%